The effect of financial leverage on dividend yield – An applied study on Saudi joint stock companies – - Al-Assire, Madi Ali (Journal of Economic, Administrative and Legal Sciences, 2022)
The study aimed to identify the impact of financial leverage on the return on dividends in Saudi joint stock companies during the period 2010-2019. The study sample consisted of (51) companies, which distributed their profits during the study years, and the study relied on the data published in the financial reports. The results of the study concluded that there is no statistically significant effect (of leverage, company size, company age) on the dividend yield, but there is a positive relationship, but it is not statistically significant. Dividend yield, but there is a negative but not statistically significant relationship. It recommended the need for companies to use borrowed funds that achieve a return on investment that exceeds the cost of financing on loans, and for financial leverage to have a tangible impact on the return on dividends. With a study that takes into account the inflation factor and the economic situation, to come up with results that benefit decision makers, whichever is more appropriate for financial leverage, financing by ownership or indebtedness, or deferring and reducing the degree of financial leverage that maximizes the return on dividends, taking into account the return on investment in companies.